Effect of anaesthesia on intraocular blood flow. Issue 2 (February 1991) - Robinson, R; White, M; McCann, P; Magner, J; Eustace, P
Abstract : Pulsatile ocular blood flow, intraocular pressure, systemic blood pressure, and heart rate was measured in two groups of 15 patients. One received lignocaine 1.5 mg/kg intravenously prior to induction. There was a significant increase in intraocular pressure after suxamethonium, which was not associated with any rise in ocular blood flow. Both the IOP and ocular blood flow increased significantly after tracheal intubation. A rise in ocular blood flow reflects the stress response associated with intubation. Lignocaine failed to attenuate either response.